THE USE OF KOREAN WORDS BY NON-NATIVE SPEAKERS IN STIKES BANYUWANGI - Wahyu Adri Wirawati (Universitas PGRI Yogyakarta, 2015)
Korean language has become one of the famous foreign languages in Indonesia. Itentered Indonesia through their culture such as songs, movies and dramas. Indonesia people, in thisstudy the students of STIKES Banyuwangi, learn the Korean language through subtitles given inevery movie and drama, and also lyrics of a song. The subtitles are usually written in English or inbahasa Indonesia, while the lyrics of a song usually written in English, Hangul (Korean alphabet) andKorean language written in Latin alphabet. Using the subtitles and the lyrics, the Indonesia people canlearn and use the Korean language. Nevertheless, their Korean language is not used appropriatelybecause they do not understand the whole meaning of a conversation and the grammar and strucure ofa sentence so they only use several words that have specific meaning. They acquire the words thatusually appear in the subtitles and try to translate it into Bahasa Indonesia by using ‘Google Translate’or dictionary. Most of the words are related to feeling and nickname in relationship. Yet, because thereis still little number of people understanding Korean language, the Indonesian teenagers only use itwith their peer who also like the Korean culture. They do not use it in a formal situation or in asituation when they know the person they speak to does not understand Korean language. When theyspeak in Korean language, code mixing appears. Entertainers, particularly singer, actor and actress,become the major factor that motivates the students to learn Korean language. It has influenced thestudents in STIKES Banyuwangi and as a result several of them use Korean words in theircommunication.